Synergistic degradation of polyethylene by a restructured bacterial consortium isolated from marine plastic debris - Zhen Rong; Jun-Qing Chen; Yue-Hong Wu; Xue-Wei Xu (Water Research, 2027)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Bioinspired orientation-regulated conductive hydrogels with hierarchical lamellar architecture for synergistic mechanical and electrical robustness - Tianhao Yu; Chao Rong; Ting Su; Shijia Wan; Bowei Zhang; Yabin Yan; Fu-Zhen Xuan (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

The poisoning mechanism of N2O reductive catalysts and anti-interference modification/regeneration technology - Wu Pengfei; Guan Bin; Zhu Lei; Zhu Tiankui; Chang Shiying; Ma Jiangli; Wang Rong; Yang Dongxia; Shu Kaiyou; Zhuang Zhongqi; Chen Junyan; Gao Junjie; et al. (Journal of Environmental Chemical Engineering, 2026)

Enhanced anaerobic biodegradation of 17α-ethinylestradiol via a flow-through electrode - Jiale Zheng; Zhen Lei; Yuan Yang; Mei Chen; Rong Chen (Bioresource Technology, 2026)

Heat stress modulates the size-dependent effects of aminated polystyrene particles on a marine diatom - Ting-Ting Xu; Zhen-Liang Li; Zhi-Yan Wang; Yu-Han Xie; Heng-Xiang Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2026)

Role of macrophage NLRP3 inflammasome activation in real-ambient particulate matter-induced abnormal hepatic glucose metabolism - Dong Wu; Zhen Zhang; Sixin Chen; Haoran Chen; Daochuan Li; Shuxin Zhang; Junjie Dou; Yuanyuan Ma; Rong Zhang; Lianhua Cui (Journal of Environmental Sciences, 2026)

Synergistic management of nitrogen-based pollutants from ammonia-fueled engines: key emission control technologies - Junjie Gao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Low temperature selective catalytic oxidation of ammonia reaction (NH3-SCO): Introducing Co, or Zr to improve comprehensive performance of the Ag/Al2O3 catalyst - Sikai Zhao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Hazardous Materials, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Granite weathering revealed by magnesium isotopes fractionation: Implications for the flux dynamics and global carbon sink - Kai Luo; Jin-Long Ma; Fang-Zhen Teng; Gang-Jian Wei; Guan-Hong Zhu; Jia-Rong Liu; Zhuo-Ying Zhang; Zhi-Bing Wang (Chemical Geology, 2026)

Optimizing lipid retention for anaerobic membrane bioreactors treating food waste: Balancing methane enhancement and membrane fouling control - Luwei Yan; Shuangquan Zhao; Yu Xi; Yaqian Liu; Yuxin Xiao; Zhen Lei; Qian Li; Rong Chen (Bioresource Technology, 2026)

Kinetic Characteristics and Migration Behavior of Fractal-Based Sub-Diffusion of Coal Reservoir Gas under Anomalous Spatio-Temporal Conditions - Zhenyang Wang; Shuo Zhang; Congmeng Hao; Lu Bai; Rong Zhang; Guanhua Ni; Zhen Liu; Zhao Li; Jiaxuan Liu (Natural Resources Research, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Docking Collision Response of an Underwater Mooring Suspension Docking System - Hua Tan; Zhen Lv; Rong Zheng; Guangzhi Zhang (Journal of Marine Science and Engineering, 2026)
Suspension docking systems offer significant application potential in autonomous underwater docking operations because of their deployment and recovery convenience. This study investigated the interaction between an axisymmetric, underactuated autonomous underwater vehicle (AUV) and a suspended guiding hood docking device (DOCK). The effects of collision velocity, collision location, collision angle, mass, and moment of inertia on the post-collision kinematic states of both bodies are analyzed. Previous studies have typically determined AUV parameters using empirical formulas, whereas few have clearly described the calibration procedure for the hydrodynamic drag coefficients of a suspended guiding hood DOCK. In this study, the hydrodynamic coefficients of both the AUV and the DOCK were determined using STAR-CCM+ and embedded into the ADAMS built-in functions to construct a physically more realistic simulation model. Subsequently, water tank experiments were conducted for suspension docking collisions. The validity of the simulation model was verified by comparing the kinematic states of the DOCK and AUV observed from the simulations and experiments. Based on the established model, the docking dynamics under various operating conditions were simulated. The simulation results indicate that the AUV mass should not exceed twice the mass of the DOCK, and the moment of inertia of the DOCK should be maximized. The risk of suspension docking failure increases significantly when the mooring line length exceeds 40 m, and the negative buoyancy of the DOCK should be at least 300 N. These findings provide critical guidance for improving the success rate of suspension docking operations.

First case report: Severe mass mortality in intensively cultured black scraper (Thamnaconus modestus) caused by nervous necrosis virus infection - Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Zhen Meng; Yingeng Wang; Xiaojun Rong; Meijie Liao; Bin Li; Wenlong Li; Xinzhang Ji; Xiaoyan Cheng; Zheng Zhang (Aquaculture, 2026)

A novel closed-loop path planning algorithm for unmanned surface vessel swarms based on potential field-guided deep Q-learning - Chunhan Zhang; Rong Zhen; Yu Zheng; Yan Zhang; Jialun Liu; Ke Zhang; Chunxu Li (Ocean Engineering, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Corrigendum to “Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control” [Fuel 418 (2026) 138729] - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Corrigendum to “Synergistic management of nitrogen-based pollutants from ammonia-fueled engines: key emission control technologies” [JFUE_138780 (2026) 260529-018277] - Junjie Gao; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Multi-technique NMR analysis of liquid CO2 hydrate growth and pore structure evolution in sediments - Yu-Hao Bu; Yi-Fei Sun; Xiao-Cun Ma; Ling-Ban Wang; Zhen-Bin Xu; Yong-Yi Zhai; Jin-Rong Zhong; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Review: From research progress to real-world marine applications of direct seawater electrolysis for hydrogen production - Yao Yao; Bin Guan; Lei Zhu; Tiankui Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Environmental Chemical Engineering, 2026)

Nitrous oxide emissions, impacts and treatment technologies: Core progress and prospects of systematic, practical and applicable studies - Luoxin Xu; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Journal of Environmental Chemical Engineering, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

Eliminating high-voltage phase transitions and oxygen loss in O3-type sodium layered cathodes via reversible solid-solution and anionic-redox chemistry - Lin-Rong Wu; Yu-Han Zhang; Zhen Wu; Hui Wu; Nian Zhang; Ding Zhang; Xiaochuan Duan; Xian-Ming Zhang (Science Bulletin, 2026)

Fe-regulated AnMBR for carbon & phosphorus co-recovery and membrane fouling control - Ying Dong; Rong Chen; Jifei Chang; Fengai Yang; Zhen Lei; Xin Wang; Nan Li (Chemical Engineering Journal, 2026)

Magnetic biochar combined with digestate bioaugmentation synergistically accelerates the recovery of a collapsed anaerobic digestion system - Bao-Shan Xing; Yong-Ning Feng; Jia-Yi Liu; Yi Zhang; Guangyin Zhen; Samir Ibrahim Gadow; Rong Chen; Xiaochang C. Wang; Yu-You Li (Chemical Engineering Journal, 2026)

Protein foundation models: a comprehensive survey - Hao Xu; Liangjie Li; Sangyu Pan; Peng Cheng; Yuxiang Wang; Zhen Rong; Feng Liu; Xingxu Huang; Shengqi Wang; Wenjie Shu (Science China Life Sciences, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

The transcription factor SlPLATZ22 negatively regulates salinity tolerance in tomato plants - Xin Li; Fei Ding; Niannian Zhou; Zheng Chen; Jiahui Huang; Fangling Jiang; Carl-Otto Ottosen; Ron Mittler; Rong Zhou; Zhen Wu (Journal of Plant Physiology, 2026)

Synergistic effects of polystyrene microplastics and 17α-methyltestosterone on immune and oxidative stress responses in the gill and liver of Gobiocypris rarus - Yibo Jia; Lu Cao; Tongyao Li; Haiyan Zhao; Gen Chen; Zijun Xiong; Weiya Rong; Qing Liu; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; et al. (Fish & Shellfish Immunology, 2026)

Design of sequential strongly convex programming algorithm for reentry trajectory planning - Yutang Li; Di Zhou; Zhen He; Songzhou Li; Siyuan Li; ChaoRan Yan; Rong Huang (Advances in Space Research, 2026)

A novel deep neural network with geographical position constraints for shallow water depth estimation - Xinle Guo; Rong Huang; Yusheng Xu; Bin Cao; Kuifeng Luan; Zhen Ye; Huan Xie; Xiaohua Tong (Marine Geodesy, 2026)

Haladaptatus marinus sp. nov., Haladaptatus rarus sp. nov., Haladaptatus ordinarius sp. nov., and Halomicrococcus pelagicus sp. nov., halophilic archaea from diverse coastal tidal flats - Xin-Ru Zhang; Jing Hou; Zhen Rong; Yue-Hong Wu; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Wheat density drives negative density dependence in nitrogen uptake and root plasticity in wheat–weed communities - Li Zhang; Weiqiang Liu; Yizhong Rong; Jiazhen Xi; Lingfeng Mao; Anna Gunina; Zhen Zhang (Rhizosphere, 2026)

Adaptive variational fusion of multi-source lunar digital elevation models based on curvature regularization - Siyi Qiu; Zhen Ye; Yusheng Xu; Jia Qian; Rong Huang; Tao Tao; Huan Xie; Xiaohua Tong (Computers & Geosciences, 2026)

Reduced graphene oxide enhances emerging contaminants removal in anaerobic wastewater treatment: Synergistic role of adsorption and microbial metabolism - Lianxu Wang; Zixin Zhang; Youfei Zhou; Zhen Lei; Yuan Yang; Yu-You Li; Rong Chen (Bioresource Technology, 2026)

Superenhancer-driven SMC4 promotes myeloma growth by epigenetically enhancing IFI16-dependent STING signaling - Jiayun Guan; Xuanyi Lin; Zhenfeng Dai; Jianbiao Zhou; Zhen Cai; Tze King Tan; Tae-Hoon Chung; Xiaochen Zhang; Wee-Joo Chng; Xiaoxiang Rong; Yunlu Jia (Apoptosis, 2026)

Estimating soil moisture at farm scale with high spatial resolution: integrating remote sensing data, and machine learning - Di Wang; Shenhan Xu; Shuai Wang; Wenhui Liu; Nanjuan Zheng; Zhen Wang; Yao Rong; Chenglong Zhang; Chaozi Wang; Nigenare Amantai; Zailin Huo (Journal of Hydrology, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Glycine Drives IMP Production in Hybrid Bream (Megalobrama Amblycephala ♀ × Culter Alburnus ♂) Via Concerted Action: Activating glycyl-tRNA Synthetase and Fueling the Pentose Phosphate Pathway - Zhehua Xu; Weiting Zhang; Ruijie Zhan; Jiefan Zhou; Man Chen; Yonghua Zhou; Fufa Qu; Rong Zhou; Shaochun Liu; Shenping Cao; Jianzhou Tang; Zhen Liu (Marine Biotechnology, 2026)

Biocontrol potential of the egg-larval parasitoid Chelonus bifoveolatus and egg parasitoid Telenomus remus against fall armyworm - Mi Huang; Zhen Shen; Yong-Ming Chen; Talha Tariq; Liang-De Tang; Qing-Rong Bai; Jian Wei; Kelvin Kamfwa; Nicolas Desneux; Lian-Sheng Zang (Crop Protection, 2026)

Peijinzhouia sedimentorum gen. Nov., sp. nov., isolated from polymetallic nodule fields of the Eastern Pacific, and proposal of the family Peijinzhouiaceae fam. Nov. - Yi-Ran Zhang; Xu-Ya Lv; Zhen Rong; Xue-Wei Xu; Yue-Hong Wu (Systematic and Applied Microbiology, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Transcriptomics and Experiments Verified that Astaxanthin Reduces the Apoptosis of Nerve Cells in Ischemic Stroke by Inhibiting the Toll-like Receptor Signaling Pathway - Shan Gao; Jinjian Li; Yuetong Zhao; Zhen Wei; Chunshu Rong; Kuiyang Zuo; Xu Wang; Dexi Zhao (Molecular Neurobiology, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Towards highly-reliable precise point positioning for maritime navigation - Zhen Gao; Rong Yang; Wenfeng Nie; Xingqun Zhan (Ocean Engineering, 2025)

Field verification of the surface renewal method for evapotranspiration measurement in arid agricultural area: The uncertainty of calibration parameter - Zhen Wang; Nanjuan Zheng; Bingbing Jiang; Yao Rong; Xin Li; Peijin Wu; Weishu Wang; Chenglong Zhang; Zailin Huo (Journal of Hydrology, 2025)

Faustmann Model Expansion Under Policy Uncertainty: Empirical Evidence from Fujian Province, China - Yan-Zhen Hong; Rong-Huan Zhang; Hai-Jie Kou; Bang-Ni Li (Small-scale Forestry, 2025)

Adaptive responses of soil phosphorus availability and plant phosphorus resorption to nitrogen enrichment-induced phosphorus limitation in a boreal peatland - Yu-Xin Ji; Le-Lin Yu; Zhen Zeng; Xian-Wei Wang; Rong Mao (Plant and Soil, 2025)

Butein attenuates cardiac fibrosis by mediating TGF-β1/Smad signaling pathway after myocardial infarction - Mengmeng Deng; Rui Ma; Jinlei Li; Pan Lu; Rong Tan; Zhen Chen; Xin Guo (Journal of Molecular Histology, 2025)

A method for detecting transgenic rapeseed using pollen collected by Apis mellifera L - Rong Yuan; Miao Wang; Zhen Li; Meiyan Hong; Li Su; Gang Wu; Xinhua Zeng (Transgenic Research, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

The dynamic succession of the core microbial communities in pasteurized milk during refrigeration based on metagenomics - Chunyan Hu; Rong Guo; Jiao Zhuang; Yan Gao; Xia Zhang; Yu Meng; Zhen Liu; Yongxia Bian; Liqing Wu; Shuai Guo; Ning Ju (International Dairy Journal, 2025)

Hydrochemical characteristics and circulation pattern of fault-type geothermal water in karst region: A case study in western Yunnan, China - Chuan Wen; Wenping Mu; Qiang Wu; Zhen Yang; Rong Li; Yubing Song; Hui Tan (Geothermics, 2025)

AIEgen-based porous organic polymer-Ag nanoparticles hybrids with coreaction accelerator amplification and covalent rigidification-enhanced electrochemiluminescence for aflatoxin M1 detection - Jun-Qi Song; Qiu-Yi Peng; Mei-Ling Lu; Shu-Zhen Gao; Wen-Bin Liang; Shaoguang Sun; Ruo Yuan; Dong-Rong Xiao (Food Chemistry, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Maritime image defogging algorithm for maritime management promotion in sea fog environment - Yubo Wang; Rong Zhen (Ocean & Coastal Management, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

Carbon dots promote tomato growth and yield via photosynthesis enhancement and leaf senescence delay - Shuang Li; Wenbo Zhao; Wei Zhao; Zhen Jiao; Keqiao Cui; Rong Wang; Aiying Wang; Yuantao Tan; Huandong Li; Yue Yin; Feijuan Gao; Kaikai Liu; et al. (Journal of Plant Physiology, 2025)

Platinum reduction in anaerobic biofilm-membrane bioreactor: Performance, mechanism, and biofilm microbial communities - Yue Wang; Zhuo Zhen; Rong Zhao; Hui Jia; Jie Wang (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Cytochrome P450-mediated biotransformation of octocrylene in Tetradesmus obliquus: Integrative insights from transcriptomics, proteomics, molecular docking, and density functional theory calculation - Jun-Jie Hu; Chang-Gui Pan; Xiang-Rong Xu; Feng-Jiao Peng; Shan Liu; Jiying Pei; Zhen-Zhu Liu; Hao Liang; Kefu Yu (Journal of Hazardous Materials, 2025)

Bundle adjustment for multi-source Mars orbiter imagery with generalized control constraints - Qionghua You; Zhen Ye; Chen Chen; Huan Xie; Yanmin Jin; Rong Huang; Changyou Xu; Yusheng Xu; Xiaohua Tong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Network-based insights into the temperature-driven mechanisms of bacterial self-assembly in the solid-state fermented vinegar seed Pei - Mingchao Jiang; Yiyang Zou; Yuhang Wang; Yunsong Yang; Dong Han; Wenting Li; Yuanyuan Zhu; Yuqin Wang; Zhen Yu; Ke Wang; Chunchi Rong; Peng Liu; et al. (Food Bioscience, 2025)

A natural 294-bp indel in the VviHKT1;1 proximal promoter influences the salt resistance of VviHKT1;1-overexpressing Arabidopsis - Fengjie Wang; Xiaoying Gong; Xuenan Zhang; Rong Zhao; Ning Han; Zhen Yang (Journal of Plant Research, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Cadmium exposure causes trophoblast abnormal syncytization and endocrine dysfunction in preeclampsia - Weilong Lin; Xuemeng Li; Xiangyou An; Jiancai Yin; Ziyan Zhao; Xiaorui Yan; Rong Xu; Baojing Zhao; Xue Du; Huiru Cheng; Zhen Yu; Yuanyuan Yang (Reproductive Toxicology, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Degradation of polyethylene by three bacteria isolated from coastal beach - Jun-Qing Chen; Zhen Rong; Dao-Qiong Zheng; Yue-Hong Wu; Xue-Wei Xu (Environmental Research, 2025)

Low Nitrogen with Split Application Strategy Enhances Antioxidative Defense, Photosynthesis, and Enzymatic Activities to Waxy Maize Under Heat Stress - Song Xu-dong; Ahmad Irshad; Zhang Hui-min; Zhang Zhen-liang; Zhou Guang-fei; Chen Guo-qing; Mao Yu-xiang; Lu Hu-hua; Hao De-rong (Journal of Plant Growth Regulation, 2025)

Construction and validation of a predictive model for the risk of multidrug-resistant Klebsiella pneumoniae infection based on machine learning algorithms - a multicenter retrospective study - Tao Sun; Pei-Pei Wang; Jun-Ji Liu; Zhen An; Jun-Rong Zhao; Jun Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

ZDHHC13 Reduces the Risk of Ischemic Stroke by Regulating Metabolites - Zhen Wei; Chunshu Rong; Wei He; Xu Wang; Dexi Zhao (Journal of Molecular Neuroscience, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

LoGAN: A novel local attentive generative adversarial resizable network for detailed 3D reconstruction of the Martian surface using monocular HiRISE images and DTMs - Jiarui Cao; Rong Huang; Yusheng Xu; Zhen Ye; Jia Qian; Ludwig Hoegner; Xiaohua Tong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Deciphering biochar-driven membrane fouling mitigation mechanisms in high-solids AnMBRs: A multi-perspective analysis using computational fluid dynamics and interface thermodynamics - Chengfan Jiao; Shaowen You; Zhen Lei; Feixiang Zan; Qian Li; Yu-You Li; Rong Chen (Chemical Engineering Journal, 2025)

Tuning ligand defect in porphyrins metal-organic frameworks to boost electrochemiluminescence for sensitive detection of amyloid-β1-42 - Jinyan Li; Xiaoqi Pei; Rong Qu; Lei Liao; Wen Zhang; Zhen Wang; Gang Xie; Sanping Chen; Jing Han (Chemical Engineering Journal, 2025)

Molecular Insight Into the Hydrolysis of Phthalate Esters by a Family IV Esterase - Zhen Rong; Li‐Guo Hong; Ying‐Yi Huo; Jixi Li; Dao‐Qiong Zheng; Yang Ha; Jeffrey Fan; Xue‐Wei Xu; Yue‐Hong Wu (Environmental Microbiology, 2025)
Phthalate esters (PAEs) are prevalent environmental contaminants, with their biodegradation efficiently driven by microorganisms through ester bond hydrolysis. This study investigates the mechanism of Poc14, a novel family IV esterase, using x‐ray crystallography, bioinformatics, biochemistry and site‐directed mutagenesis. Phylogenetic analysis classifies Poc14 as a family IV esterase with conserved catalytic motifs crucial for its activity. Poc14 retains over 80% activity at 50°C for 4 h and tolerates up to 5% methanol or DMF, though surfactants like Tweens inhibit its function. Poc14 activity is independent of metal ions, and the addition of EDTA further enhances its activity by approximately 130%. The 1.8 Å crystal structure reveals a CAP domain and two substrate channels. Enzyme assays show Poc14 hydrolyses short‐chain diethyl phthalate (DEP) ( K m = 0.068 mM, V max = 9975 μM/min/mg) but not long‐chain di(2‐ethylhexyl) phthalate (DEHP) due to steric hindrance. Molecular docking assessed Poc14's potential to hydrolyse DEP and DEHP after residue mutations, resulting in the Poc14‐AAG variant. Poc14‐AAG could hydrolyse one bond of DEHP and diester bonds of DEP. Our study positions Poc14 as a promising enzyme for environmental remediation, with potential for optimising DEHP degradation and exploring dimerisation effects.

Effective feature matching of high-resolution planetary orbiter images based on optimized image partitioning and rapid local correspondence - Lin Xue; Zhen Ye; Dayong Liu; Shijie Liu; Rong Huang; Huan Xie; Yongjiu Feng; Beibei Guo; Yusheng Xu; Xiaohua Tong (Planetary and Space Science, 2025)

Biochar supported metal cobalt activated PAA to efficiently degrade CBZ: The important role of Co (IV) in the generation of peroxyacyl radicals - Mengyu Li; Shaochun Yuan; Yuhang Liu; Siqi Chen; Mingyang Si; Rong Liu; Bangxing Ren; Zhe Zhang; Zhen Liu (Journal of Water Process Engineering, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

The deficiency of virulence factor AerA in Aeromonas veronii alleviates intestinal injury and microbiota disorders in largemouth bass (Micropterus salmoides) - Lu-Chuan Zhao; Ze-Sheng Zhang; Zhen-Zhen Yuan; Hui-Min Zhang; Jing-Bao Yang; Qian-Rong Liang; Shun-Fa Yi; Meng-Meng Huang; Hui Fei; Shun Yang (Fish & Shellfish Immunology, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Identification of key risk ships in risk-based ship complex network - Qian Qiao; Rong Zhen; Han Dong; Shuwu Wang; Qionglin Fang (Ocean Engineering, 2025)

Secondary scattering shape from shading for precise terrain reconstruction of the lunar permanently shadowed regions - Jia Qian; Zhen Ye; Siyi Qiu; Rong Huang; Huan Xie; Yusheng Xu; Xiaohua Tong (Icarus, 2025)

Delocalization state-induced C-O bond weakness for enhancing CO2 electroreduction to CO - Rong Wang; Yue Peng; Deli Chen; Chuan Gao; Houlin Wang; Zhen Chen; Junhua Li (Chemical Engineering Journal, 2025)

Pyroptosis was suppressed by 20-hydroxyecdysone through Lin28b-mediated let-7d in vascular endothelial cells - Danli Chen; Jianjun Yang; Lingxuan Ren; Zihan Zheng; Zhen Jin; Jiazheng Wen; Jianyu He; Rongcheng Ding; Jianjiang Wang; Rong Lin; Qiang Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unlocking China's grain yield potential: Harnessing technological and spatial synergies in diverse cropping systems - Zhen-Zhong Dai; Sen Chang; Guo-Rong Zhao; Jia-Jia Duan; Hao-Yuan Liang; Zhi-Yuan Zhu; Sheng-Li Liu; Yong-Zhong Feng; Xing Wang (Agricultural Systems, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Investigation into the reaction mechanism for enhanced peracetic acid catalytic decomposition by coexisting hydrogen peroxide under electrochemical conditions - Siqi Chen; Zhen Liu; Mengyu Li; Bangxing Ren; Rong Liu; Chuanliang Zhao; Yuhang Liu; Zhe Zhang; Xiaodi Duan; Yao Chen (Process Safety and Environmental Protection, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Modeling hydrous mineral distribution on Mars with extremely sparse data: A multi-scale spatial association modeling framework - Leilei Jiao; Peng Luo; Rong Huang; Yusheng Xu; Zhen Ye; Sicong Liu; Shijie Liu; Xiaohua Tong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Large-scale crop dataset and deep learning-based multi-modal fusion framework for more accurate G × E genomic prediction - Qixiang Zou; Shuaishuai Tai; Qianguang Yuan; Yating Nie; Heping Gou; Longfei Wang; Chuanxiu Li; Yi Jing; Fangchun Dong; Zhen Yue; Yi Rong; Xiaodong Fang; et al. (Computers and Electronics in Agriculture, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Petrogenesis and geodynamic implications of gabbroic diorites of the early Paleozoic Mijiashan ophiolite in the eastern North Qilian Orogenic Belt, NW China - Jiao-Long Zhao; Liang Liu; Qing-Yan Tang; Jin-Rong Wang; Zhen-Xi Yang; Pei-Qing Hu; Xin-Wei Zhai; Saniye Abdereyimu; Zi-Han Dang (Journal of Asian Earth Sciences, 2025)

Extraction of short-chain fatty acid ethyl Ester in Baijiu using covalent organic framework–based magnetic nanoparticles: Theoretical screening and experimental validation - Xiaolong Shang; Ying Han; Xudong Lian; Siting Ye; Ling Ao; Baoguo Sun; Rong Liu; Pan Zhen; Yongqing Zhang; Yintao Jia; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Plant venation-inspired bio-based adhesive with toughness, wide temperature adaptability, and long-term adhesion - Dongna Li; Xiaoge Ye; Zhen Li; Shiyao Huang; Rong Zhao; Xiaojun Ma; Jianing Li; Fen Yin (Chemical Engineering Journal, 2025)

Fusion of multiple photogrammetric DEMs for large-scale lunar topographic mapping - Rong Huang; Wenhui Ding; Yusheng Xu; Zhen Ye; Siyan Xu; Miyu Zhou; Xiaohua Tong (Advances in Space Research, 2025)

Biorecovery of platinum group metals to nanoparticles: Current status, prospects, and challenges - Yue Wang; Zhuo Zhen; Rong Zhao; Jie Yang; Hui Jia; Jie Wang (Journal of Environmental Chemical Engineering, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Optimization of Inbound and Outbound Vessel Scheduling in One-Way Channel Based on Reinforcement Learning - Rong Zhen; Meng Sun; Qionglin Fang (Journal of Marine Science and Engineering, 2025)
As the size and number of ships continue to grow, effective management of vessel scheduling has become more and more important for the efficient one-way channel port operation, whose characteristics significantly affect the safety and efficiency of ports. This paper presents a reinforcement-learning-based approach to optimize the scheduling of vessels in a one-way channel, aiming to quickly identify a scheduling solution that enhances port operational efficiency. This method models the vessel scheduling problem in a one-way channel by incorporating navigational constraints, safety requirements, and vessel-specific characteristics. Using the Q-learning algorithm to minimize vessel wait times, it identifies an optimal scheduling solution. Experiments were conducted using real data from the Dayao Bay Pier of Dalian Port to validate the rationality and effectiveness of the proposed model and algorithm. The results show that the reinforcement learning approach achieved approximately a 16% improvement in solution quality compared to the genetic algorithm (GA) while requiring only half the computation time. Additionally, it reduced delay times by over 40% relative to the traditional FCFS strategy, indicating superior overall performance. This research presents an efficient, intelligent approach to vessel scheduling, providing a theoretical foundation for further advancements in this field and enhancing decision support for vessel scheduling in one-way channels with practical implications.

Epilimnetic oligotrophication increases contribution of oxic methane production to atmospheric methane flux from stratified lakes - Fan Xun; Muhua Feng; Cheng Zhao; Wenlei Luo; Xiaotong Han; Zhen Ci; Yifan Yin; Rong Wang; Qinglong L. Wu; Hans-Peter Grossart; Peng Xing (Water Research, 2025)

3D morphometry of Martian craters from HRSC DEMs using a multi-scale semantic segmentation network and morphological analysis - Peiqi Ye; Rong Huang; Yusheng Xu; Wendi Li; Zhen Ye; Xiaohua Tong (Icarus, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Characterization of a Novel Tn7-like Transposon Carrying blaDHA-1 in Providencia stuartii MF1 Isolated from Swine Wastewater - Shijie Ou; Xinyi Tian; Zhen Zhang; Lingjia Zhu; Rong Wang; Guangxiang Cao; Jiafang Fu; Peipei Zhang (Current Microbiology, 2025)

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part II: Madden–Julian oscillation - Zhen Fu; Yi Zhang; Xiaohan Li; Congwen Zhu; Hongbo Liu; Xinyao Rong; Chengming Li (Climate Dynamics, 2025)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Mechanism of β-MnO2 particle for the peroxymonosulfate activation under electric field: the promoting effect of carbamazepine on Mn(III) and reactive oxygen species production - Shaochun Yuan; Shuquan He; Qingyu Wu; Tuo Wang; Mengyu Li; Rong Liu; Yao Chen; Chuanliang Zhao; Fei Liu; Zhen Liu (Process Safety and Environmental Protection, 2024)

A novel collaborative collision avoidance decision method for multi-ship encounters in complex waterways - Han Dong; Rong Zhen; Qiyong Gu; Zhong Lin; Jiuhu Chen; Kai Yan; Bing Chen (Ocean Engineering, 2024)

Integrative transcriptomic analysis reveals a broad range of toxic effects of triclosan on coral Porites lutea - Hao Liang; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Rong-Gui Zhu; Chao-Yang Zhou; Zhen-Zhu Liu; Kefu Yu (Journal of Hazardous Materials, 2024)

A deeper investigation of membrane fouling in anaerobic membrane bioreactors for wastewater treatment: Influencing factors and fouling layer characteristics - Xiaohuan Yang; Zhen Lei; Lianxu Wang; Rong Chen (Journal of Environmental Management, 2024)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

p-Smad3 differentially regulates the cytological behavior of osteoclasts before and after osteoblasts maturation - Jiapeng Ye; Zhen Hua; Jirimutu Xiao; Yang Shao; Shaoshuo Li; Heng Yin; Mao Wu; Yi Rong; Bowen Hong; Yang Guo; Yong Ma; Jianwei Wang (Molecular Biology Reports, 2024)

Synergic treatment of domestic wastewater and food waste in an anaerobic membrane bioreactor demo plant: Process performance, energy consumption, and greenhouse gas emissions - Zhen Lei; Jiale Zheng; Jiale Liu; Qian Li; Jingjing Xue; Yuan Yang; Zhe Kong; Yu-You Li; Rong Chen (Water Research, 2024)

Promotion of aromatic amino acids of extracellular polymeric substance targeted transformation via sulfite mediated iron redox cycling in sludge solid-liquid separation - Jiahao Lai; Huan Liu; Zhen Yang; Rong Deng; Yun Xiong; Yafei Li; Min Song (Water Research, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Recovery of platinum nanoparticles by the anaerobic mixed consortium: Platinum (IV) ion reduction, microbial community dynamics and functional genes identification - Yue Wang; Rong Zhao; Zhuo Zhen; Jie Yang; Hui Jia; Jie Wang (Journal of Water Process Engineering, 2024)

Characteristics and fouling behaviors of soluble microbial products and sub-visible particles in an anaerobic membrane bioreactor treating sewage at room temperature - Jiale Zheng; Wen Wen; Zhen Lei; Rong Chen (Journal of Water Process Engineering, 2024)

Rhodamine and related substances in food: Recent updates on pretreatment and analysis methods - Rong-zhu Du; Yuan Zhang; Yu Bian; Chun-yu Yang; Xue-song Feng; Zhen-wei He (Food Chemistry, 2024)

Fate and drivers of mariculture-derived microplastics from ponds to mangrove forests - Zhen Zhao; Yihua Wei; Yijin Wang; Gen Peng; Eddy Y. Zeng; Kefu Yu; Xiang-Rong Xu; Ruilong Li (Environmental Pollution, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Enhancing vitamin D3 bioaccessibility: Unveiling hydrophobic interactions in soybean protein isolate and vitamin D3 binding via an infant in vitro digestion model - Jia-Rong Huang; Jing-Ru Song; Wan-Shuang Cai; Zhen-Wen Shao; Da-Yong Zhou; Liang Song (Food Chemistry, 2024)

Rapid adsorptive removal of emerging and legacy per- and polyfluoroalkyl substances (PFASs) from water using zinc chloride-modified litchi seed-derived biochar - Zhen-Zhu Liu; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Hong-Ming Tan; Rong-Gui Zhu; Chao-Yang Zhou; Hao Liang; Kefu Yu (Bioresource Technology, 2024)

Altered Function and Structure of the Cerebellum Associated with Gut–Brain Regulation in Crohn’s Disease: a Structural and Functional MRI Study - Yunfei Li; Yanling Zheng; Lan Rong; Yan Zhou; Zhen Zhu; Qian Xie; Zonghui Liang; Xiaohu Zhao (The Cerebellum, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Environmental changes impact on vegetables physiology and nutrition – Gaps between vegetable and cereal crops - Rong Zhou; Fangling Jiang; Yi Liu; Xiaqing Yu; Xiaoming Song; Zhen Wu; Davide Cammarano (Science of The Total Environment, 2024)

Water-soluble metal-organic cages crosslinked injectable hydrogel for multi-modal synergistic therapy - Wen-Zhen Li; Xiao-Fan Rong; Yu Wang; Jia-Wen Xiong; Na Zhou; Zi-Xin Wang; Xi-Jia Fang; Wenjing Wang; Yi Liu; Xiao-Qiang Wang (Chemical Engineering Journal, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

An appetite assessment method for fish in outdoor ponds with anti-shadow disturbance - Weiqiang Ni; Dan Wei; Zequn Peng; Zhen Ma; Songming Zhu; Rong Tang; Xuelei Tian; Jian Zhao; Zhangying Ye (Computers and Electronics in Agriculture, 2024)

Deciphering the role of extracellular polymeric substances in the adsorption and biotransformation of organic micropollutants during anaerobic wastewater treatment - Lianxu Wang; Zhen Lei; Zixin Zhang; Xiaohuan Yang; Rong Chen (Water Research, 2024)

Extraction, structural characterization, and antioxidant activity of polysaccharides from three microalgae - Yang Zhao; Chun Han; Yangyingdong Wu; Qianchen Sun; Meng Ma; Zhen Xie; Rong Sun; Haiyan Pei (Science of The Total Environment, 2024)

Dynamic characteristics of deep-sea single-point mooring levitation docking system - Rong Zheng; Hua Tan; Zhen Lv; Han Xu; Zhou Yu (Ocean Engineering, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part I: mean state - Zhen Fu; Yi Zhang; Xiaohan Li; Xinyao Rong (Climate Dynamics, 2024)

PBA alleviates cadmium-induced mouse spermatogonia apoptosis by suppressing endoplasmic reticulum stress - Rong Wang; Mengyuan Li; Zhen Wu; Wenjing Gong; Mingming Zhang; Yehao Liu; Yuyou Yao; Yanli Ji (Toxicology in Vitro, 2024)

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Regulation of wheat growth by soil multifunctionality and metagenomic-based microbial functional profiles under mulching treatments - Yang Liu; Rui Liu; Zhen Feng; Rong Hu; Fazhu Zhao; Jun Wang (Science of The Total Environment, 2024)

The influence of biochar from animal and plant on the transformation of phosphorus during paper mill sludge composting - Siming Zhong; Zhen Yu; Xiaoming Liu; Meihua Zhao; Hongwei Rong (Environmental Science and Pollution Research, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Regional ship collision risk prediction: An approach based on encoder-decoder LSTM neural network model - Chenyan Lin; Rong Zhen; Yanting Tong; Shenhua Yang; Shengkai Chen (Ocean Engineering, 2024)

Efficient magnetic enrichment cascade single-step RPA-CRISPR/Cas12a assay for rapid and ultrasensitive detection of Staphylococcus aureus in food samples - Yujie Ma; Hongjuan Wei; Yunxiang Wang; Xiaodan Cheng; Hong Chen; Xingsheng Yang; Hongsheng Zhang; Zhen Rong; Shengqi Wang (Journal of Hazardous Materials, 2024)

TiO2-x modified Ni/SBA-15 catalysts for dibenzofuran hydrodeoxygenation - Yu-Kun Wang; Hao-Wei Li; Yu-Rong Liu; Zi-Zheng Xie; Zhen-Yi Du; Xing-Bao Wang; Wen-Ying Li (Chemical Engineering Journal, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Optimization of ultrasound-assisted extraction of glycyrrhizic acid and glabridin from Glycyrrhiza glabra L. using response surface methodology and development of a green analytical method - Ye-fei Liang; Qing Wen; Zhen-fei Yang; Cui-qin Li; Fa-rong Li (Sustainable Chemistry and Pharmacy, 2024)

Quantitative structure-biotransformation relationships of organic micropollutants in aerobic and anaerobic wastewater treatments - Lianxu Wang; Zhen Lei; Sining Yun; Xiaohuan Yang; Rong Chen (Science of The Total Environment, 2024)

Determination of tetrodotoxin in bivalve mollusks by hydrophilic interaction liquid chromatography-triple quadrupole mass spectrometry with internal standard calibration and its contamination in Zhejiang province, China - Ming-rong Qian; Hui-zhen Wu; Zeng-xuan Cai; Mei-jia Xu; Jian-long Han; Xiao-min Xu (Food Chemistry, 2024)

PDA-mediated colorimetric-fluorescence co-enhanced immunochromatography assay for the simultaneous and rapid detection of SARS-CoV-2 and HAdV - Xingsheng Yang; Xiaodan Cheng; Zhijie Tu; Hongjuan Wei; Zhen Rong (Chemical Engineering Journal, 2024)

RTK ramp faults detection and exclusion by the hybrid control chart - Zhen Gao; Xingqun Zhan; Rong Yang (Advances in Space Research, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Degradation of low-density polyethylene by the bacterium Rhodococcus sp. C-2 isolated from seawater - Zhen Rong; Zhi-Hao Ding; Yue-Hong Wu; Xue-Wei Xu (Science of The Total Environment, 2024)

A novel deterministic search-based algorithm for multi-ship collaborative collision avoidance decision-making - Rong Zhen; Ziqiang Shi; Qiyong Gu; Shenhua Yang (Ocean Engineering, 2024)

Ecosystem health evaluation of urban rivers based on multitrophic aquatic organisms - Zhen Cui; Wenting Fan; Cheng Chen; Kangle Mo; Qiuwen Chen; Qiang Zhang; Rong He (Journal of Environmental Management, 2024)

Predicting the velocity and trajectory of a rockfall after collision considering the effects of slope properties - Shao-Zhen Duan; Guang-Li Li; Xin Yang; Xin-Rong Wei (Natural Hazards, 2024)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

Oligo (ethylene glycol) side chain engineering: An efficient way for boosting the development of green-solvent processable electrochromic devices - Shiyi Li; Qilin Wang; Yuehui Zhai; Zhen Xing; Jundong Zhong; Danming Chao; Xuanbo Zhu; Changru Rong; Zongquan Wu; Zheng Chen (Chemical Engineering Journal, 2023)

Enantioselective effect of the chiral fungicide tebuconazole on the microbiota community and antibiotic resistance genes in the soil and earthworm gut - Chao-Feng Li; Yi-Rong Zhang; Zhen-Chao Tan; Hui-Juan Xu; Cheng-Lan Liu (Science of The Total Environment, 2023)

ZC3H4 governs epithelial cell migration through ROCK/p-PYK2/p-MLC2 pathway in silica-induced pulmonary fibrosis - Rong Jiang; Yichao Zhou; Qianqian Gao; Lei Han; Zhen Hong (Environmental Toxicology and Pharmacology, 2023)

Failure Modes of Jointed Granite Subjected to Weak Dynamic Disturbance Under True-Triaxial Compression - Ben-Guo He; Lei Wang; Xia-Ting Feng; Rong-Li Zhen (Rock Mechanics and Rock Engineering, 2023)

An improved detection method of GNSS faults with fractional information divergence - Zhen Gao; Xingqun Zhan; Rong Yang (Advances in Space Research, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Sludge granulation in PN/A enhances nitrogen removal from mainstream anaerobically pretreated wastewater - Zhen Lei; Jingjing Xue; Yongning Feng; Yu-You Li; Zhe Kong; Rong Chen (Science of The Total Environment, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Graphene oxide-based colorimetric/fluorescence dual-mode immunochromatography assay for simultaneous ultrasensitive detection of respiratory virus and bacteria in complex samples - Xiaodan Cheng; Xingsheng Yang; Zhijie Tu; Zhen Rong; Chongwen Wang; Shengqi Wang (Journal of Hazardous Materials, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Oxalic acid–modified activated carbons under hydrothermal condition for the adsorption of the 2-butanone - Naijing Bu; Xiaomeng Liu; Tianzhen Li; Rong Li; Qiang Zhen (Environmental Science and Pollution Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Identifying influential ships in multi-ship encounter situation complex network based on improved WVoteRank approach - Yanting Tong; Rong Zhen; Han Dong; Jialun Liu (Ocean Engineering, 2023)

Application of colorimetric sensor array combined with visible near-infrared spectroscopy for the matcha classification - Qin Ouyang; Yanna Rong; Jiaqi Wu; Zhen Wang; Hao Lin; Quansheng Chen (Food Chemistry, 2023)

Influence of GI configurations and wall thermal effects on flow structure and pollutant dispersion within urban street canyons - Peng-Yi Cui; Rong Ji; Lai He; Zhen Zhang; Yang Luo; Yong Yang; Yuan-Dong Huang (Building and Environment, 2023)

Relationship between daily variations of methane emissions and eructation peaks in dairy cows measured with an automated head-chamber system - Rong Wang; Yu Rong Cao; Xiu Min Zhang; Fan Zhang; Xu Tian; Rong Zhen Zhong; Zhi Liang Tan; Min Wang (Animal Feed Science and Technology, 2023)

Cadmium induced a non-coding RNA microRNA535 mediates Cd accumulation in rice - Erkui Yue; Fuxi Rong; Zhen Liu; Songlin Ruan; Tao Lu; Haifeng Qian (Journal of Environmental Sciences, 2023)

Faba bean above-ground biomass and bean yield estimation based on consumer-grade unmanned aerial vehicle RGB images and ensemble learning - Yishan Ji; Rong Liu; Yonggui Xiao; Yuxing Cui; Zhen Chen; Xuxiao Zong; Tao Yang (Precision Agriculture, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

An Improved A-Star Ship Path-Planning Algorithm Considering Current, Water Depth, and Traffic Separation Rules - Rong Zhen; Qiyong Gu; Ziqiang Shi; Yongfeng Suo (Journal of Marine Science and Engineering, 2023)
The influence of the maritime environment such as water currents, water depth, and traffic separation rules should be considered when conducting ship path planning. Additionally, the maneuverability constraints of the ship play a crucial role in navigation. Addressing the limitations of the traditional A-star algorithm in ship path planning, this paper proposes an improved A-star algorithm. Specifically, this paper examines the factors influencing ship navigation safety, and develops a risk model that takes into account water currents, water depth, and obstacles. The goal is to mitigate the total risk of ship collisions and grounding. Secondly, a traffic model is designed to ensure that the planned path adheres to the traffic separation rules and reduces the risk of collision with incoming ships. Then, a turning model and smoothing method are designed to make the generated path easy to track and control for the ship. To validate the effectiveness of the proposed A-star ship path-planning algorithm, three cases are studied in simulations and representative operational scenarios. The results of the cases demonstrate that the proposed A-star ship path-planning algorithm can better control the distance to obstacles, effectively avoid shallow water areas, and comply with traffic separation rules. The safety level of the path is effectively improved.

An improved RRT algorithm based on prior AIS information and DP compression for ship path planning - Qiyong Gu; Rong Zhen; Jialun Liu; Chen Li (Ocean Engineering, 2023)

Insights into the role of ·OH generated in Fe2+/CaO2/coal slime system for efficient extracellular polymeric substances degradation to improve dewaterability of sewage sludge - Rong Deng; Jiahao Lai; Zonghao Liu; Bing Song; Huan Liu; Dandan Chen; Gancheng Zuo; Zhen Yang; Fanyue Meng; Tingting Gong; Min Song (Chemosphere, 2023)

In-depth profiling of di(2-ethylhexyl) phthalate metabolic footprints in rats using click chemistry-mass spectrometry probes - Yu-Ning Hu; Jin-Tao Zhan; Pei-Rong Bai; Na An; Jun-Jie Tan; Yan-Zhen Wang; Quan-Fei Zhu; Yu-Qi Feng (Journal of Hazardous Materials, 2023)

Corrigendum to ’ Biochar enhances the biotransformation of organic micropollutants (OMPs) in an anaerobic membrane bioreactor treating sewage’ [Water Research 223 (2022) 118974] - Zhen Lei; Shixin Zhang; Lianxu Wang; Qian Li; Yu-You Li; Xiaochang C. Wang; Rong Chen (Water Research, 2023)

Effects of a calcium/vitamin D/Zinc combination on anti-osteoporosis in ovariectomized rats - Shanshan Wang; Zhen Luo; Hujie Luo; Zhiwei Li; Zhengqiang Yuan; Jian Tang; Li Lin; Zhiyun Du; Jin-Rong Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Real-ambient particulate matter exposure-induced FGFR1 methylation contributes to cardiac dysfunction via lipid metabolism disruption - Benying Li; Yanan Liang; Hongxu Bao; Daochuan Li; Ying Zhang; Xinyu Dun; Zijian Xu; Andong Ji; Zhen Zhang; Yahui Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Molecular identification of a flavone synthase I/flavanone 3β-hydroxylase bifunctional enzyme from fern species Psilotum nudum - Jie Fu; Piao-Yi Wang; Rong Ni; Jiao-Zhen Zhang; Ting-Ting Zhu; Hui Tan; Jing Zhang; Hong-Xiang Lou; Ai-Xia Cheng (Plant Science, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

Effect of Nrf2 loss on senescence and cognition of tau-based P301S mice - Ruben Riordan; Wang Rong; Zhen Yu; Grace Ross; Juno Valerio; Jovita Dimas-Muñoz; Valeria Heredia; Kathy Magnusson; Veronica Galvan; Viviana I. Perez (GeroScience, 2023)

A Novel Intelligent Ship Detection Method Based on Attention Mechanism Feature Enhancement - Yingdong Ye; Rong Zhen; Zheping Shao; Jiacai Pan; Yubing Lin (Journal of Marine Science and Engineering, 2023)
The intelligent perception ability of the close-range navigation environment is the basis of autonomous decision-making and control of unmanned ships. In order to realize real-time perception of the close-range environment of unmanned ships, an enhanced attention mechanism YOLOv4 (EA-YOLOv4) algorithm is proposed. First of all, on the basis of YOLOv4, the convolutional block attention module (CBAM) is used to search for features in channel and space dimensions, respectively, to improve the model’s feature perception of ship targets. Then, the improved-efficient intersection over union (EIoU) loss function is used to replace the complete intersection over union (CIoU) loss function of the YOLOv4 algorithm to improve the algorithm’s perception of ships of different sizes. Finally, in the post-processing of algorithm prediction, soft non-maximum suppression (Soft-NMS) is used to replace the non-maximum suppression (NMS) of YOLOv4 to reduce the missed detection of overlapping ships without affecting the efficiency. The proposed method is verified on the large data set SeaShips, and the average accuracy rate of mAP0.5–0.95 reaches 72.5%, which is 10.7% higher than the original network YOLOv4, and the FPS is 38 frames/s, which effectively improves the ship detection accuracy while ensuring real-time performance.

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

A Novel Intelligent Detection Algorithm of Aids to Navigation Based on Improved YOLOv4 - Rong Zhen; Yingdong Ye; Xinqiang Chen; Liangkun Xu (Journal of Marine Science and Engineering, 2023)
Aiming at the problem of high-precision detection of AtoN (Aids to Navigation, AtoN) in the complex inland river environment, in the absence of sufficient AtoN image types to train classifiers, this paper proposes an automatic AtoN detection algorithm Aids-to-Navigation-YOLOv4 (AN-YOLOv4) based on improved YOLOv4 (You Only Look Once, Yolo). Firstly, aiming at the problem of an insufficient number of existing AtoN datasets, the Deep Convolutional Generative Adversarial Networks (DCGAN) is used to expand and enhance the AtoN image dataset. Then, aiming at the problem of small target recognition accuracy, the image pyramid is used to multi-scale zoom the dataset. Finally, the K-means clustering algorithm is used to correct the candidate box of AN-YOLOv4. The test on the test dataset shows that the improvement effect of AN-YOLOv4 is obvious. The accuracy rate of small targets is 92%, and the average accuracy (mAP) of eight different types of AtoN is 92%, which is 14% and 13% higher than the original YOLOv4, respectively. This research has important theoretical significance and reference value for the intelligent perception of the navigation environment under the intelligent shipping system.

A novel fuzzy multi-factor navigational risk assessment method for ship route optimization in costal offshore wind farm waters - Rong Zhen; Peilin Lv; Ziqiang Shi; Guoquan Chen (Ocean & Coastal Management, 2023)

Molecular docking and molecular dynamics simulation study on the toxicity mechanism of bongkrekic acid - Hongmei Li; Zhen Liang; Ying Li; Jiazhen Wen; Rong Zhang (Toxicon, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Refractory organics removal in PMS and H2O2/PMS oxidation system activated by biochar/nZVI/MoS2 composite: Synthesis, performance, mechanism and dosing methods - Hao Sun; Baoyong Zhang; Na Wang; Nianbo Zhang; Yunqian Ma; Lihua Zang; Zhen Li; Rong Xue (Journal of Environmental Chemical Engineering, 2023)

New insights into the cleaning mechanisms of conductive membrane by NaClO and electric field in terms of protein and polysaccharide degradation - Rong Huang; Tong Zhang; Qiaoying Wang; Hongbo Gu; Zhen Zhou; Zhichao Wu; Zhiwei Wang (Chemical Engineering Journal, 2023)

An integrated process for co-producing fermentable sugars and xylonate from sugarcane bagasse based on xylonic acid assisted pretreatment - Zhen Zhu; Rong Huang; Shuangquan Yao; Yiruo Liu; Qibo Zhang; Xin Zhou; Kankan Jiang (Bioresource Technology, 2023)

Carrier type affects anammox community assembly, species interactions and nitrogen conversion - Baoyong Zhang; Nianbo Zhang; Ao He; Chen Wang; Zhen Li; Guanjun Zhang; Rong Xue (Bioresource Technology, 2023)

Formation of Sn-rich granitic magma: a case study of the highly evolved Kafang granite in the Gejiu tin polymetallic ore district, South China - Ke-Ke Sun; Jun Deng; Qing-Fei Wang; Bin Chen; Rong Xu; Zhen-Fei Ma (Mineralium Deposita, 2023)

Functional insights of a two-component system sensor kinase GacS in a fish pathogen, Pseudomonas plecoglossicida - Su-Ming Zhou; Yan Wang; Feng-Ling Shu; Zhen Tao; Xiao Xie; Jia-Song Xie; Rong-Rong Ma; Fei Yin (Aquaculture, 2023)

Mechanical and microscopic properties of soil according to the rate of increase in pore water pressure - Zhao Duan; Zhen-Yan Li; Yan-Bin Wu; Bing Niu; Rong-Jian Shen (Soil and Tillage Research, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

A strategy for screening and identification of new amino acid-conjugated bile acids with high coverage by liquid chromatography-mass spectrometry - Yan-Zhen Wang; Peng-Cheng Mei; Pei-Rong Bai; Na An; Jin-Gang He; Jie Wang; Quan-Fei Zhu; Yu-Qi Feng (Analytica Chimica Acta, 2023)

Modification of TiO2 by Er3+ and rGO enhancing visible photocatalytic degradation of arsanilic acid - Xinghao Ren; Hang Yao; Rui Tang; Rong A; Shoujun Yuan; Wei Wang; Ibrahim Mohamed Ali; Zhen-Hu Hu (Environmental Science and Pollution Research, 2022)

Molecular Characterization and Dietary Regulation of Glutaminase 1 (gls1) in Triploid Crucian Carp (Carassius auratus) - Yangbo Xiao; Rong Huang; Shenping Cao; Dafang Zhao; Zhuangwen Mao; Chuchu Xiao; Zhehua Xu; Xiaomei Zhou; Xinran Zhang; Yu Zhang; Jianzhou Tang; Junyan Jin; et al. (Fishes, 2022)
Kidney-type glutaminase, encoded by the gls1 gene, plays a critical role in glutamate production and improvement of meat flavor. In this study, a gls1 gene encoding 595 amino acids was cloned from triploid crucian carp (Carassius auratus) (TCC) and showed a high similarity with the gls1 gene found in Cyprinus carpio, Sinocyclocheilus rhinocerous and Puntigrus tetrazona. Comparing the abundance of gls1 in different tissues, we found its expression level in the brain and liver were significantly higher than that in heart, gut, kidney, spleen and muscle. gls1 expression in the brain reached the highest value. In addition, the expression levels of gls1 also appeared different in diurnal variation, with the highest expression seen at 9:00, while it was low at 3:00, 6:00, 15:00 and 24:00. Furthermore, dietary regulation of gls1 expression was investigated in our study. In each feeding trial, each diet was randomly assigned to triplicate tanks. Fish were fed one of the tested diets up to satiation twice daily. The results showed that gls1 expression increased in 32% protein group and decreased in 35–41% protein group. The results of different protein source experiments showed that the expression of gls1 gene in the mixed protein group (the control group) was significantly higher than that in the fish meal and soybean meal groups. Glutamate treatment revealed that appropriate concentrations (0.10 mg/mL in vivo and 2.00% in vitro) of glutamate remarkably improved the expression of gls1. Besides, diets supplemented with 0.80–1.60% lysine-glutamate dipeptide exhibited a down regulatory impact on gls1 expression. In conclusion, this study demonstrated that the expression of gls1 in TCC was increased by 32% protein diet, mixed protein source diet and diet with 2.00% glutamate concentration, while decreased by 0.80–1.60% lysine-glutamate dipeptide. The findings of this study provide a reference for the regulation of gls1 and have a potential application in the optimization of dietary formula in aquaculture.

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Plasma Exo-miRNAs Correlated with AD-Related Factors of Chinese Individuals Involved in Aβ Accumulation and Cognition Decline - Lifang Wang; Hefu Zhen; Yuzhe Sun; Shuang Rong; Benchao Li; Zhijie Song; Zhili Liu; Zhiming Li; Jiahong Ding; Huanming Yang; Xiuqing Zhang; Haixi Sun; et al. (Molecular Neurobiology, 2022)
Numerous studies have investigated the risk factors of Alzheimer’s disease (AD); however, AD-risk factors related miRNAs were rarely reported. In this study, AD-risk factor related miRNAs of 105 Chinese individuals (45 AD patients and 60 cognitively normal controls) were investigated. The results showed that Hsa-miR-185-5p, Hsa-miR-20a-5p, and Hsa-miR-497-5p were related to AD and education, Hsa-miR-185-5p, Hsa-miR-181c-5p, Hsa-miR-664a-3p, Hsa-miR-27a-3p, Hsa-miR-451a, and Hsa-miR-320a were related to AD and depression. Target prediction of above miRNAs showed that these miRNAs were involved in the generation and clearance of amyloid-beta (Aβ), important molecules related to cognition, and disease-activated microglia response to AD. It is worth noting that Hsa-miR-185-5p was related to both education and depression, whose decreased expression pattern in AD patients was alleviated by education and enhanced by depression, and participates in Aβ generation and accumulation. Our results indicated that certain education and depression factors can contribute to AD progression by modulating miRNA expression, implying that preventive interventions might alter AD progression in Chinese patients.

Abscisic acid induces the expression of AsKIN during the recovery period of garlic cryopreservation - Xiaodong Xing; Min Liu; Fangling Jiang; Rong Zhou; Yunhe Bai; Hanyu Wei; Deng Zhang; Jingjing Wei; Zhen Wu (Plant Cell Reports, 2022)

Immobilization of Chitosanase on Magnetic Nanoparticles: Preparation, Characterization and Properties - Yimeng Cheng; Zhaoyue Li; Huihui Sun; Ling Zhao; Zhen Liu; Rong Cao; Qi Liu; Xiangzhao Mao (Journal of Ocean University of China, 2022)

Fast forward modeling of muon transmission tomography based on model voxelization ray energy loss projection - Rong-Qing Zhang; Zhen-Zhu Xi; Wei Liu; He Wang; Zi-Yan Yang (Applied Geophysics, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Fbxw17 is dispensable for viability and fertility in mice - Zhen Chen; Dupeng Ma; Tingyu Jin; Ziqi Yu; Jiong Li; Qi Sun; Zejia Li; Ziye Du; Rong Liu; Yi Li; Mengcheng Luo (Molecular Biology Reports, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Bmal1- and Per2-mediated regulation of the osteogenic differentiation and proliferation of mouse bone marrow mesenchymal stem cells by modulating the Wnt/β-catenin pathway - Jiawen Zheng; Lanxin Zhang; Zhen Tan; Qing Zhao; Xiaoyu Wei; Yuqing Yang; Rong Li (Molecular Biology Reports, 2022)

Impacts of Human Activities and Climate Change on Water Storage Changes in Shandong Province, China - Longyun Deng; Zhen Han; Weixing Pu; Rong Bao; Zheye Wang; Quanyuan Wu; Jianmin Qiao (Environmental Science and Pollution Research, 2022)

Three new C 21 steroidal glycosides isolated from Metaplexis japonica and their potential inhibitory effects on tyrosine protein kinases - Xu Wang; Qing-Yun Ma; Chen Liu; Jia Yang; Qing-Tao Lv; Zhen-Hua Tian; Hai-Qiang Jiang; Rong Rong (Natural Product Research, 2022)

Brain cellular senescence in mouse models of Alzheimer’s disease - Angela O. Dorigatti; Ruben Riordan; Zhen Yu; Grace Ross; Rong Wang; Nadjalisse Reynolds-Lallement; Kathy Magnusson; Veronica Galvan; Viviana I. Perez (GeroScience, 2022)

Effect of biochar on transformation of dissolved organic matter and DTPA-extractable Cu and Cd during sediment composting - Meihua Zhao; Caiyuan Cai; Zhen Yu; Hongwei Rong; Chaosheng Zhang; Shungui Zhou (Environmental Science and Pollution Research, 2022)

Monitoring the behavior of subway tunnels during early operation in saturated soft strata - Ben-Guo He; Rong-Li Zhen; Tian-Yu Chen; Hong-Pu Li (Bulletin of Engineering Geology and the Environment, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Efficient separation and recovery of Re(VII) from Re/U bearing acidic solutions using aminotriazole modified cellulose microsphere adsorbents - Di Wen; Rong Hua; Zhen Dong; Kangjun Xie; Wei Qi; Long Zhao (Environmental Science and Pollution Research, 2021)

Characteristics of expanded polystyrene microplastics on island beaches in the Pearl River Estuary: abundance, size, surface texture and their metals-carrying capacity - Qun Xie; Heng-Xiang Li; Lang Lin; Zhen-Liang Li; Jian-sheng Huang; Xiang-Rong Xu (Ecotoxicology, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Recombinant L-HN Fusion Antigen Derived from the L and HN Domains of Botulinum Neurotoxin B Stimulates a Protective Antibody Response Against Active Neurotoxin - Zhen Li; Jian-Sheng Lu; Shan Liu; Rong Wang; Qing Xu; Yun-Zhou Yu; Zhi-Xin Yang (Neurotoxicity Research, 2021)

Effects of drought and heat on the productivity and photosynthetic characteristics of alpine meadow plants on the Qinghai-Tibetan Plateau - Li Ma; Zhong-hua Zhang; Bu-qing Yao; Zhen Ma; Xiao-tao Huang; Bing-rong Zhou; Man-hou Xu; Jing Guo; Hua-kun Zhou (Journal of Mountain Science, 2021)

A Novel Hybrid Fuel Consumption Prediction Model for Ocean-Going Container Ships Based on Sensor Data - Zhihui Hu; Tianrui Zhou; Mohd Tarmizi Osman; Xiaohe Li; Yongxin Jin; Rong Zhen (Journal of Marine Science and Engineering, 2021)
Accurate, reliable, and real-time prediction of ship fuel consumption is the basis and premise of the development of fuel optimization; however, ship fuel consumption data mainly come from noon reports, and many current modeling methods have been based on a single model; therefore they have low accuracy and robustness. In this study, we propose a novel hybrid fuel consumption prediction model based on sensor data collected from an ocean-going container ship. First, a data processing method is proposed to clean the collected data. Secondly, the Bayesian optimization method of hyperparameters is used to reasonably set the hyperparameter values of the model. Finally, a hybrid fuel consumption prediction model is established by integrating extremely randomized tree (ET), random forest (RF), Xgboost (XGB) and multiple linear regression (MLR) methods. The experimental results show that data cleaning, the size of the dataset, marine environmental factors, and hyperparameter optimization can all affect the accuracy of the model, and the proposed hybrid model provides better predictive performance (higher accuracy) and greater robustness (smaller standard deviation) as compared with a single model. The proposed hybrid model should play a significant role in ship fuel consumption real-time monitoring, fault diagnosis, energy saving and emission reduction, etc.

Establishment and optimization of a high-throughput mimic perfusion model in ambr® 15 - Lu Jin; Zhen-Shou Wang; Yun Cao; Rui-Qiang Sun; Hang Zhou; Rong-Yue Cao (Biotechnology Letters, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

Removal of boron from water by GO/ZIF-67 hybrid material adsorption - Guangzhuang Hu; Wei Zhang; Yuantao Chen; Cheng Xu; Rong Liu; Zhen Han (Environmental Science and Pollution Research, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Blumea hunanensis (Asteraceae: Inuleae), a new species from Hunan, China - Lin-Dong Duan; Yun Lin; Zhi-Rong Yang; Zhen Lu (Kew Bulletin, 2020)

Regulatory mechanisms and therapeutic potential of microglial inhibitors in neuropathic pain and morphine tolerance - Er-rong Du; Rong-ping Fan; Li-lou Rong; Zhen Xie; Chang-shui Xu (Journal of Zhejiang University-SCIENCE B, 2020)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Coordinated regulation of three kinds of thermotolerance in tomato by antioxidant enzymes - Mintao Sun; Fangling Jiang; Rong Zhou; Benjian Cen; Zhen Wu (Acta Physiologiae Plantarum, 2019)

Comprehensive meta-analysis and co-expression network analysis identify candidate genes for salt stress response in Arabidopsis - Luoyan Zhang; Zhen Zhang; Xuejie Zhang; Yan Yao; Rong Wang; Benyao Duan; Shoujin Fan (Plant Biosystems, 2019)

Oxidative damage and antioxidant mechanism in tomatoes responding to drought and heat stress - Rong Zhou; Lingpeng Kong; Xiaqing Yu; Carl-Otto Ottosen; Tongmin Zhao; Fangling Jiang; Zhen Wu (Acta Physiologiae Plantarum, 2019)

Association between serum somatostatin levels and glucose-lipid metabolism in the Jino ethnic minority and Han Chinese population - Shiyun Wang; Rong Zhang; Xuhong Hou; Fusong Jiang; Jie Wang; Zhen He; Feng Jiang; Cheng Hu; Weiping Jia (Science China Life Sciences, 2018)

Simultaneous nitrification–denitrification and microbial community profile in an oxygen-limiting intermittent aeration SBBR with biodegradable carriers - Lijuan Feng; Rong Jia; Zhen Zeng; Guangfeng Yang; Xiangyang Xu (Biodegradation, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Evaluation of temperature stress tolerance in cultivated and wild tomatoes using photosynthesis and chlorophyll fluorescence - Rong Zhou; Zhen Wu; Xu Wang; Eva Rosenqvist; Yinlei Wang; Tongmin Zhao; Carl-Otto Ottosen (Horticulture, Environment, and Biotechnology, 2018)

Complete nucleotide sequence of a new carlavirus in chrysanthemums in China - Rong Wang; Jiali Dong; Zhen Wang; Tao Zhou; Yong Li; Wanlong Ding (Archives of Virology, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Protective effect of the total flavonoids from Apocynum venetum L. on carbon tetrachloride-induced hepatotoxicity in vitro and in vivo - Wei Zhang; Zheng Dong; Xiujuan Chang; Cuihong Zhang; Guanghua Rong; Xudong Gao; Zhen Zeng; Chunping Wang; Yan Chen; Yihui Rong; Jianhui Qu; Ze Liu; et al. (Journal of Physiology and Biochemistry, 2018)

Phenotyping of faba beans (Vicia faba L.) under cold and heat stresses using chlorophyll fluorescence - Rong Zhou; Benita Hyldgaard; Xiaqing Yu; Eva Rosenqvist; Rosina Magaña Ugarte; Shanxiang Yu; Zhen Wu; Carl-Otto Ottosen; Tongmin Zhao (Euphytica, 2018)

Anti-oral common pathogenic bacterial active acetylenic acids from Thesium chinense Turcz - Chang Liu; Xiao-Tian Li; Rong-Rong Cheng; Zhu-Zhen Han; Li Yang; Zhong-Chen Song; Zheng-Tao Wang (Journal of Natural Medicines, 2018)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Changes in the Intestinal Microbiota of Gibel Carp (Carassius gibelio) Associated with Cyprinid herpesvirus 2 (CyHV-2) Infection - Rong She; Tong-Tong Li; Dan Luo; Jia-Bao Li; Liu-Yi Yin; Huan Li; Yao-Min Liu; Xiang-Zhen Li; Qi-gui Yan (Current Microbiology, 2017)

Asymmetric evolution of El Niño and La Niña: the recharge/discharge processes and role of the off-equatorial sea surface height anomaly - Zeng-Zhen Hu; Arun Kumar; Bohua Huang; Jieshun Zhu; Rong-Hua Zhang; Fei-Fei Jin (Climate Dynamics, 2017)

Erratum to: Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Rutin–Nickel Complex: Synthesis, Characterization, Antioxidant, DNA Binding, and DNA Cleavage Activities - Aun Raza; Shumaila Bano; Xiuquan Xu; Rong Xian Zhang; Haider Khalid; Furqan Muhammad Iqbal; Changkun Xia; Jian Tang; Zhen Ouyang (Biological Trace Element Research, 2017)

Association between hyperhomocysteinemia and stroke with atherosclerosis and small artery occlusion depends on homocysteine metabolism-related vitamin levels in Chinese patients with normal renal function - Guan-Hui Wu; Fan-Zhen Kong; Xiao-Feng Dong; De-Feng Wu; Qian-Zhu Guo; Ai-Rong Shen; Qing-Zhang Cheng; Wei-Feng Luo (Metabolic Brain Disease, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Preconditioned prestack plane-wave least squares reverse time migration with singular spectrum constraint - Chuang Li; Jian-Ping Huang; Zhen-Chun Li; Rong-Rong Wang (Applied Geophysics, 2017)

Repeated pre-training sleep restriction in adolescent rats impaired spatial performance - Su-Rong Yang; Huan-Xin Sun; Zhen-Zhen Hu; Si-Heng Wang; Hui Sun; Yin-Jia Xue; Chen-Bo Ye (Sleep and Biological Rhythms, 2017)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Three-Dimensional Tricuspid Annular Motion Analysis from Cardiac Magnetic Resonance Feature-Tracking - Shuang Leng; Meng Jiang; Xiao-Dan Zhao; John Carson Allen; Ghassan S. Kassab; Rong-Zhen Ouyang; Ju-Le Tan; Ben He; Ru-San Tan; Liang Zhong (Annals of Biomedical Engineering, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

The composition of pericarp, cell aging, and changes in water absorption in two tomato genotypes: mechanism, factors, and potential role in fruit cracking - Zeen Yang; Zhen Wu; Chuan Zhang; Enmei Hu; Rong Zhou; Fangling Jiang (Acta Physiologiae Plantarum, 2016)

DNA-Binding, Photocleavage, and Photodynamic Anti-cancer Activities of Pyridyl Corroles - Zhen-Hua Liang; Hai-Yang Liu; Rong Zhou; Zao Zhang; Atif Ali; Bing-Jie Han; Yun-Jun Liu; Xin-Yan Xiao (The Journal of Membrane Biology, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

Comparison of seven colchicine-induced tetraploid clones with their original diploid clones in purple coneflower (Echinacea purpurea L.) - Rong Chen; Wei-zhen Jiang; Qing-ling Li; Xin-lian Li; Xiao-lu Chen; Yue-sheng Yang; Hong Wu (Euphytica, 2016)

Heavy metals in wild marine fish from South China Sea: levels, tissue- and species-specific accumulation and potential risk to humans - Jin-Ling Liu; Xiang-Rong Xu; Zhen-Hua Ding; Jia-Xi Peng; Ming-Hua Jin; You-Shao Wang; Yi-Guo Hong; Wei-Zhong Yue (Ecotoxicology, 2015)

Transformation of the endophytic fungus Acremonium implicatum with GFP and evaluation of its biocontrol effect against Meloidogyne incognita - Yu-Rong Yao; Xue-Liang Tian; Bao-Ming Shen; Zhen-Chuan Mao; Guo-hua Chen; Bing-Yan Xie (World Journal of Microbiology and Biotechnology, 2015)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.

Synthesis and Evaluation of a Targeted Nanoglobular Dual-Modal Imaging Agent for MR Imaging and Image-Guided Surgery of Prostate Cancer - Mingqian Tan; Zhen Ye; Daniel Lindner; Susann M. Brady-Kalnay; Zheng-Rong Lu (Pharmaceutical Research, 2014)

Attenuation of Reserpine-Induced Pain/Depression Dyad by Gentiopicroside Through Downregulation of GluN2B Receptors in the Amygdala of Mice - Shui-bing Liu; Rong Zhao; Xu-sheng Li; Hong-ju Guo; Zhen Tian; Nan Zhang; Guo-dong Gao; Ming-gao Zhao (NeuroMolecular Medicine, 2014)

The rare intracellular RET mutation p.S891A in a Chinese Han family with familial medullary thyroid carcinoma - Xiao-Ping Qi; Rong-Xin Zhang; Jin-Lin Cao; Zhen-Guang Chen; Hang-Yang Jin; Ren-Rong Yang (Journal of Biosciences, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

Sphingomonas gimensis sp. nov., a novel Gram-negative bacterium isolated from abandoned lead–zinc ore mine - Guang-Da Feng; Song-Zhen Yang; Yong-Hong Wang; Guo-Zhen Zhao; Ming-Rong Deng; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Environmental Investigations and Molecular Typing of Aspergillus in a Chinese Hospital - Jun-hong Ao; Zhen-feng Hao; He Zhu; liang Wen; Rong-ya Yang (Mycopathologia, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Cerebral vasculopathy in a Chinese family with neurofibromatosis type I mutation - Jian-Tao Liang; Li-Rong Huo; Yu-Hai Bao; Zhen-Yu Wang; Feng Ling (Neuroscience Bulletin, 2013)

The effect of three culture methods on intensive culture system of pacific white shrimp (Litopenaeus vannamei) - Zhen Ma; Rong Wan; Xiefa Song; Lei Gao (Journal of Ocean University of China, 2013)

Survey of aflatoxin M1 in raw milk in the five provinces of China - Nan Zheng; Jia-Qi Wang; Rong-Wei Han; Yun-Peng Zhen; Xiao-Min Xu; Peng Sun (Food Additives & Contaminants Part B-Surveillance, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Resolvin E1 Inhibits Neuropathic Pain and Spinal Cord Microglial Activation Following Peripheral Nerve Injury - Zhen-Zhong Xu; Temugin Berta; Ru-Rong Ji (Journal of Neuroimmune Pharmacology, 2013)

Why is the molybdenum-substituted tungsten-dependent formaldehyde ferredoxin oxidoreductase not active? A quantum chemical study - Rong-Zhen Liao (JBIC Journal of Biological Inorganic Chemistry, 2013)

Cathepsin L in the orange-spotted grouper, Epinephelus coioides: molecular cloning and gene expression after a Vibrio anguillarum challenge - Jing-Zhen Liang; Ying-Zhu Rao; Zhao-Rong Lun; Ting-Bao Yang (Fish Physiology and Biochemistry, 2012)

Tetrandrine citrate eliminates imatinib-resistant chronic myeloid leukemia cells in vitro and in vivo by inhibiting Bcr-Abl/β-catenin axis - Xiao-hua Xu; Yi-chao Gan; Gen-bo Xu; Ting Chen; Hong Zhou; Jin-fen Tang; Ying Gu; Fei Xu; Ying-ying Xie; Xiao-ying Zhao; Rong-zhen Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Protective effect of whey protein hydrolysates against hydrogen peroxide-induced oxidative stress on PC12 cells - Qiu-Xiang Zhang; Yu-Fang Ling; Zhen Sun; Li Zhang; Hui-Xin Yu; Samuel Mburu Kamau; Rong-Rong Lu (Biotechnology Letters, 2012)

Emerging role of berbamine as an anti-cancer agent in systemic malignancies besides chronic myeloid leukemia - Shailendra Kapoor; Yun Liang; Xi Qiu; Rong-zhen Xu; Xiao-ying Zhao (Journal of Zhejiang University-SCIENCE B, 2012)

Experimental study on the effect of waves on netting panels at a range of angles to the wave direction - Wei-hua Song; Zhen-lin Liang; Rong Wan; Fen-Fang Zhao; Kinoshita Takeshi; Liu-yi Huang; Jia-zhi Ma; Bo-hai Chen (Fisheries Science, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

A Pyrene-based Highly Selective Turn-on Fluorescent Sensor for Copper(II) Ion and its Application in Live Cell Imaging - Shu-Pao Wu; Zhen-Ming Huang; Shi-Rong Liu; Peter Kun Chung (Journal of Fluorescence, 2012)

Interleukin-6, but Not Soluble Adhesion Molecules, Predicts a Subsequent Mortality from Cardiovascular Disease in Patients with Acute ST-Segment Elevation Myocardial Infarction - Zhen-Xing Fan; Qi Hua; Yin-Ping Li; Rong-Kun Liu; Zheng Yang (Cell Biochemistry and Biophysics, 2011)

Chlorothalonil degradation by Ochrobactrum lupini strain TP-D1 and identification of its metabolites - Xiu-Zhen Shi; Rong-Jun Guo; Kazuhiro Takagi; Zuo-Qing Miao; Shi-Dong Li (World Journal of Microbiology and Biotechnology, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Berbamine inhibits proliferation and induces apoptosis of KU812 cells by increasing Smad3 activity - Yun Liang; Xi Qiu; Rong-zhen Xu; Xiao-ying Zhao (Journal of Zhejiang University-SCIENCE B, 2011)

Theoretical investigation of the first-shell mechanism of acetylene hydration catalyzed by a biomimetic tungsten complex - Yan-Fang Liu; Rong-Zhen Liao; Wan-Jian Ding; Jian-Guo Yu; Ruo-Zhuang Liu (JBIC Journal of Biological Inorganic Chemistry, 2011)

Prognostic value of serum soluble Fas in patients with locally advanced unresectable rectal cancer receiving concurrent chemoradiotherapy - Qi-lian Liang; Zhou-yu Li; Guo-qiang Chen; Zhen-nan Lai; Bi-rong Wang; Jie Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of immune activation on the retrieval of spatial memory - Zhen-Bo Huang; Hao Wang; Xiu-Rong Rao; Tao Liang; Jing Xu; Xiang-Sheng Cai; Guo-Qing Sheng (Neuroscience Bulletin, 2010)

Inhalable Microparticles as Carriers for Pulmonary Delivery of Thymopentin-Loaded Solid Lipid Nanoparticles - Yan-Zhen Li; Xun Sun; Tao Gong; Jie Liu; Jiao Zuo; Zhi-Rong Zhang (Pharmaceutical Research, 2010)

Comparison of reproductive strategies in two externally ovipositing non-pollinating fig wasps - Zhen-Ji Wang; Feng-Ping Zhang; Yan-Qiong Peng; Li-Fen Bai; Da-Rong Yang (Symbiosis, 2010)

A preliminary study of the Six-Item Screener in detecting cognitive impairment - Mei-Rong Chen; Qi-Hao Guo; Xin-Yi Cao; Zhen Hong; Xiao-Hong Liu (Neuroscience Bulletin, 2010)

Stability and Biodistribution of a Biodegradable Macromolecular MRI Contrast Agent Gd-DTPA Cystamine Copolymers (GDCC) in Rats - Xueming Wu; Yuda Zong; Zhen Ye; Zheng-Rong Lu (Pharmaceutical Research, 2010)

Improvement of heat and drought photosynthetic tolerance in wheat by overaccumulation of glycinebetaine - Gui-Ping Wang; Zhen Hui; Feng Li; Mei-Rong Zhao; Jin Zhang; Wei Wang (Plant Biotechnology Reports, 2010)

Karyotype and genetic relationship based on RAPD markers of six wild buckwheat species (Fagopyrum spp.) from southwest of China - Xiao-yan Yang; Zhen-Fang Wu; Hui Chen; Ji-rong Shao; Qi Wu (Genetic Resources and Crop Evolution, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Mechanism of the Formation for Thoracic Impedance Change - Ming-Xing Kuang; Qiu-Jin Xiao; Chao-Ying Cui; Nan-Zhen Kuang; Wen-Qin Hong; Ai-Rong Hu (Annals of Biomedical Engineering, 2010)

Relationship between transmembrane signal transduction pathway and DNA repair and the mechanism after global cerebral ischemia-reperfusion in rats - Rong-Liang Xue; Jia-Xuan He; Ning Wang; Feng-Zhen Yao; Jian-Rui Lv; Gang Wu (Neuroscience Bulletin, 2009)

Molecular mapping of a major QTL conferring resistance to SCMV based on immortal RIL population in maize - Xiao-Hong Liu; Zhen-Bo Tan; Ting-Zhao Rong (Euphytica, 2009)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Development and evaluation of immunoassay for zeranol in bovine urine - Yuan Liu; Cun-zhen Zhang; Xiang-yang Yu; Zhi-yong Zhang; Xiao Zhang; Rong-rong Liu; Xian-jin Liu; Zhen-ming Gong (Journal of Zhejiang University-SCIENCE B, 2007)

Changes of Porcine Growth Hormone and Pituitary Nitrogen Monoxide Production as a Response to Cadmium Toxicity - Xin-Yan Han; Qi-Chun Huang; Bo-Jing Liu; Zi-Rong Xu; Yi-Zhen Wang (Biological Trace Element Research, 2007)

ARC contributes to the inhibitory effect of preconditioning on cardiomyocyte apoptosis - Yu Zhen Li; Xiu Hua Liu; Xiao Mei Zhu; Li Rong Cai (Apoptosis, 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)

Berbamine induces apoptosis in human hepatoma cell line SMMC7721 by loss in mitochondrial transmembrane potential and caspase activation - Guan-yu Wang; Jia-wei Zhang; Qing-hua Lü; Rong-zhen Xu; Qing-hua Dong (Journal of Zhejiang University-SCIENCE B, 2007)

Cytogenetic Study of a Trigeneric (Triticale × Trileymus) Hybrid - Xing-Feng Li; Zhen-Qiao Song; Shu-Bing Liu; Ju-Rong Gao; Hong-Gang Wang (Euphytica, 2006)

Ovipositor length of threeApocrypta species: Effect on oviposition behavior and correlation with syconial thickness - Wen-Quan Zhen; Da-Wei Huang; Jin-Hua Xiao; Da-Rong Yang; Chao-Dong Zhu; Hui Xiao (Phytoparasitica, 2005)

Cloning, expression and genomic structure of a novel human GNB2L1 gene, which encodes a receptor of activated protein kinase C (RACK)* - Shu Wang; Jin-zhong Chen; Zhen Zhang; Shaohua Gu; Chaoneng Ji; Rong Tang; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Detection of the organophosphorus nerve agent sarin by a competitive inhibition enzyme immunoassay - Yong-xin Zhou; Qing-jin Yan; Yun-xiang Ci; Zhen-quan Guo; Kang -Tai Rong; Wen-bao Chang; Yu-fen Zhao (Archives of Toxicology, 1995)

Production, characterization and application of monoclonal antibodies against the organophosphorus nerve agent Vx - Yun-xiang Ci; Yong-xin Zhou; Zhen-quan Guo; Kang -Tai Rong; Wen-bao Chang (Archives of Toxicology, 1995)